2010
DOI: 10.1111/j.1600-0560.2009.01407.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraepidermal and dermal Merkel cell carcinoma with squamous cell carcinoma in situ: a case report with review of literature

Abstract: Merkel cell carcinoma (MCC), a rare aggressive primary cutaneous neuroendocrine carcinoma, occurs on sun-damaged skin, especially in the elderly. Its unique co-expression of cytokeratin 20 (CK20) and neuroendocrine markers, including neuron-specific enolase (NSE), is diagnostic. Most MCCs are located in the dermis, rarely has an intraepidermal component been reported. We report a case of MCC with an intraepidermal component admixed with squamous cell carcinoma in situ (SCCIS). We were able to identify the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…It has been reported that some cases of MCC are concurrent with Bowen disease occurring in the same region synchronously2,5-9. Several studies suggested that arsenic is a carcinogen that may induce the occurrence of MCC in addition to squamous cell carcinoma, basal cell carcinoma, and Bowen disease7,8,12.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that some cases of MCC are concurrent with Bowen disease occurring in the same region synchronously2,5-9. Several studies suggested that arsenic is a carcinogen that may induce the occurrence of MCC in addition to squamous cell carcinoma, basal cell carcinoma, and Bowen disease7,8,12.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologically, the epidermis is involved in less than 10% of all MCC cases, and the tumor cells are located in the dermis and grow toward subcutaneous tissue, with a tendency to infiltrate vascular and lymphatic vessels1,2. The tumor cells are uniformly sized basophilic cells, with round or oval nuclei and small nucleoli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It mimicked an eccrine carcinoma. Sirikanjanapong et al [26] reported a case of intraepidermal and dermal MCC with squamous cell carcinoma in situ. Hwang et al [27] reported a case of MCC with squamous and sarcomatous differentiations.…”
Section: Discussionmentioning
confidence: 99%